ANALISIS TEMPERING DENGAN QUENCHING MEDIA OLI MESRAN SAE 40 TERHADAP SIFAT MEKANIK POROS S 45 C - Suwandono .; Ahmad Farid; Heriy Kuswanto (Universitas Pancasakti Tegal, 2011)
This research intends to know the influence of temper and quenching cooling media of oli mesran SAE40 towards the characteristic of machine of stell S45C. The proses of temper is conducted in 300C with the holding time 60 minute while the process of quenching is conducted in 870C with the holding time 30 minute.The method used in this research is descriptive. The raw material for the specimen is stell S45C, imported by PT.TIRA AUSTENITE. The specimen of pull test use standard JIS Z 2204 and hardness use standard JIS Z2245. The chemical composition testing shows that steel S45C enter in the medium carbon steel with the content carbon 0,44%. The result of tensile strength of steel S45C after heating by temper-quenching by using the two different medias of temper, those are free air which result of the tensile strength is 1096,86 N/mm2, it is higher than oil which result is 783,38 N/mm2. However, the average elongation of free air is 3,62% with the average contraction 32,36%. It is smaller than the average elongation of oil that is 7,18% with the average contaction 48,96%. The average result of strength testing temper media of free air is 185,33 HB. It is bigger than the average result of temper test by using oil that is 173 HB. From the result of the steel testing, the temper-quenching by using oil as the media is suggested to be used if we want to produce the steel with a high level of the though, so that the steel is easier to be formed.Key words: quenching, tempering, tensile strength of shaf S45C.